Systematic Review of Chinese Traditional Exercise Baduanjin Modulating the Blood Lipid Metabolism. (12th November 2012) - Mei, Lijuan; Chen, Qingyue; Ge, Li; Zheng, Guohua; Chen, Jinxiu
Abstract : Background . Baduanjin exercise is considered to be beneficial to modulate the blood lipid metabolism. The purpose of the systematic review was to assess the potential efficacy and safety of Baduanjin exercise. Methods . MEDLINE, EMBASE, CBM, CNKI, VIP, Chinese Important Conference Papers Database, and Chinese Dissertation Database were searched for all prospective-controlled trials of Baduanjin exercise from their inception to December 31, 2011. Results . A total of 14 studies were included. Comparing with no treatment, Baduanjin exercise significantly reduced the levels of TC, TG, LDL-C in plasma, and elevated plasma HDL-C level for healthy participants, and the pooled MD (95% confidence interval, CI) was −0.58 mmol/L (−0.86, −0.30 mmol/L), −0.22 mmol/L (−0.31, −0.13 mmol/L), −0.35 mmol/L (−0.54, −0.17 mmol/L), 0.13 mmol/L (0.06, 0.21 mmol/L), respectively. Baduanjin exercise also obviously decreased the levels of TG, LDL-C in plasma comparing with no treatment for patients, and the pooled MD (95% CI) was −0.30 mmol/L (−0.40, −0.19 mmol/L), −0.38 mmol/L (−0.63, −0.13 mmol/L), but there was not obvious to decrease plasma TC level or elevate plasma HDL-C level in patients with the pooled MD (95%CI), −0.39 mmol/L (−1.09, 0.31 mmol/L) and 0.22 mmol/L (−0.11, 0.55 mmol/L), respectively. In addition, the obvious advantage was not observed to modulate the blood lipid metabolism in comparing Baduanjin exercise with other exercises, regardless for health participants or patients. Conclusion . Studies indicated that Baduanjin exercise could significantly decrease the levels of TC, TG, LDL-C levels in plasma and elevate plasma HDL-C level for the healthy people. It also was helpful that Baduanjin exercise modulated the blood lipid metabolism for patients. Moreover, the Baduanjin exercise did not have an obvious advantage on modulating the lipid metabolism comparing with other exercises. But the evidence was uncertain because of the small sample size and low-methodological quality.